Upgrading Pemahaman Aplikasi CAT dan Bedah Tes Intelegensi Umum Untuk Seleksi CPNS - Fitri, Diah Angraina; Susilawati, Susilawati; Sari, Rafika (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2023)
Along with the times, applications on computers are increasingly sophisticated. Knowledge of the Computer Assisted Test method is very important for civil servant candidate fighters who will take the test. After passing the administrative selection, CPNS selection fighters are required to take part in the next selection which consists of 3 tests, namely the Personal Characteristics Test (TKP), General Intelligence Test ( TIU) and National Insight Test (TWK). At this time there are still many people who fail to take the CPNS selection test. One of the areas where there are still many failures when participating in the CPNS selection is Meskom village. Meskom Village is located in Bengkalis Regency, Riau. The problem that is often faced by the community is failure when taking the CPNS CAT (Computer Assisted Test) test, therefore training needs to be held regarding the application used during the CPNS test selection. In addition, this training also helps the community in solving CPNS selection questions, one of which is the general intelligence test. Training and application of the CAT (Computer Assisted Test) application as well as discussion of personality tests and national insight tests as preparation for the implementation of the CPNS test for the people of Meskom village. This activity succeeded in providing a simulation of the use of the CAT application to the residents of the Meskom village, CPNS fighters. In addition, they are also equipped with an understanding of how to answer questions quickly and accurately according to the time available.